Staying Active While Staying Home: The Use of Physical Activity Technologies During Life Disruptions - Newbold, Joseph W.; Rudnicka, Anna; Cox, Anna (Frontiers in Digital Health, 2021)
One impact of the Covid-19 lockdowns was a restriction on people's ability to engage in physical activity in previously routine ways. This paper presents a two-stage mixed-method study exploring how people used technology to stay physically active during this period. We found that activity trackers reminded people to be active, while virtual coaching (i.e., video tutorials and online classes) helped them stay connected. The lockdown increased people's awareness of their activity levels and removed barriers to exercise, for example by giving them greater control over their time. However, it also created new challenges, with lack of time and space, injuries due to sudden changes in activity, and anxiety around lockdown, putting limits on physical activity. We highlight future directions that must be addressed to maximise the benefits of physical activity technologies for people trying to stay active during major life disruptions.